Robust detection of translocations in lymphoma FFPE samples using targeted locus capture-based sequencing - Amin Allahyar (Nature Portfolio, 2021)
Preservation of cancer biopsies by FFPE introduces DNA fragmentation, hindering analysis of rearrangements. Here the authors introduce FFPE Targeted Locus Capture for identification of translocations in preserved samples.